Analysis of Postal Traffic as the Basis for Redesigning Postal Network - Gašpert, Milica; Miletić, Ruža; Bošnjak, Ivan (Promet - Traffic&Transportation, 2012)
Analysis of the traffic flows of postal items is an impmtantprerequisite in improving the technology and/or redesigningpostal network.The basic modelling sequence is to optimise the traffic(postal) network structure for the identified traffic demand andthe determined traffic flow matrix, respecting relevant requirementsand limitations.The paper provides elements of a general approach to solvingthe problem and develops a concrete traffic matrix with thedata on postal-item flows. Elements are indicated for redesigningof postal network, which include the positioning of nodesequipped by systems of automatic handling of postal items.